(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Textbook selection presents a conundrum for history as a school subject. On one hand it is desirable that the best textbooks are available to be used in classrooms, on the other selection appears to imply control over what can be studied, or even bias and state interference. This is a case study of the textbook screening of Grade 12 history textbooks conducted by the Department of Education in January 2007, in which the author was a participant. It is based upon the criteria and evaluation report forms for the 10 books that were submitted for approval. The article is in three parts: a description of the selection criteria employed by the department and a discussion of the issues that they raise in terms of selected literature on textbook assessment in history; an analysis of the way in which the selection criteria were used in the textbook screening process followed by a discussion of what it concerns; and, in conclusion, a consideration of the place and importance of textbook selection to history education.